Significados do processo gestacional na vivência da família - Stumm, Karine Eliel (2012)
Considering pregnancy as a family experience, cultural baggage implies directly on referrals to be made in each specific situation. Comprehending this, the nurse can direct her care, singularizing it. So, the main aim of this study is to know how it s the pregnancy experience of families about the process of pregnancy whose women are assisted in Kennedy Sanitary Unit, in the city of Santa Maria/RS. We developed a field, descriptive, qualitative study with cultural approach. Research subjects were five pregnant women and five family members that develop prenatal nursing consults, on Kennedy Primary Care Unit (KPCU), in the city of Santa Maria/RS. As data collect instrument, we used semi-structured interview and observation. Data were analyzed according to Minayo in theme analysis. We followed the norms of Resolution nº 196/96 Of the National Health Board of Ministry of Health. The results will be presented in the form of three articles. Article 1: The family and the gestational process: experiences and meanings; Article 2: The experience of pregnancy from the perspective of family members of pregnant women: a descriptive study; Article 3: Prenatal care from the perspective of pregnant women and families. The experience of pregnancy gives several meanings for both the mother and for his family, unique to each individual, but dependent on socialization and cohabitation between members of a family unit. Should include the family in prenatal care, as this along with the pregnant woman experiences the whole experience of pregnancy.